2015
DOI: 10.1371/journal.pone.0143657
|View full text |Cite
|
Sign up to set email alerts
|

Tie2-Expressing Monocytes Are Associated with Identification and Prognoses of Hepatitis B Virus Related Hepatocellular Carcinoma after Resection

Abstract: BackgroundTie2-expressing monocytes (TEMs) are found in various tumors, involved in forming tumor blood vessels and expressing several important proangiogenic factors. The goals of this study were to evaluate the value of TEMs in diagnosing and predicting the prognosis of hepatitis B virus (HBV)-related hepatocellular carcinoma (HCC).MethodsFlow cytometry was performed to identify and count TEMs in peripheral blood monocytes from HCC patients (n = 84) receiving hepatectomy, HBV cirrhotic patients (n = 21), ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 22 publications
1
23
1
Order By: Relevance
“…TEMs are a subgroup of circulating and tumor-infiltrating myeloid cells with potency to promote angiogenesis in xenotransplanted human tumors [ 6 ]. Previous studies [ 9 , 15 ] defined TEMs as CD14+CD16+Tie2+ cells and reported that they were increased in HCC patients.TEMs are generally considered as a novel biomarker and potential therapeutic target for the diagnosis of HCC. However, reports about TEMs in healthy individuals have been controversial [ 6 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…TEMs are a subgroup of circulating and tumor-infiltrating myeloid cells with potency to promote angiogenesis in xenotransplanted human tumors [ 6 ]. Previous studies [ 9 , 15 ] defined TEMs as CD14+CD16+Tie2+ cells and reported that they were increased in HCC patients.TEMs are generally considered as a novel biomarker and potential therapeutic target for the diagnosis of HCC. However, reports about TEMs in healthy individuals have been controversial [ 6 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tie2 expression occurs, and is partially maintained, during differentiation in human neural stem cells (7), but not in mature neurons (8). Dysregulated Tie2 expression has also been observed in several tumor tissues, including oral squamous cell carcinoma, breast, gastric, leukemia and thyroid cancer (9)(10)(11)(12)(13). These studies revealed that Tie2 expression is associated with the identification and prognosis of these cancer types (12).…”
Section: Introductionmentioning
confidence: 99%
“…Dysregulated Tie2 expression has also been observed in several tumor tissues, including oral squamous cell carcinoma, breast, gastric, leukemia and thyroid cancer (9)(10)(11)(12)(13). These studies revealed that Tie2 expression is associated with the identification and prognosis of these cancer types (12). Ang1 is a secreted ligand for Tie2 that maintains vascular plasticity, perturbations in which can contribute to abnormal vascular growth (4).…”
Section: Introductionmentioning
confidence: 99%
“…Chemotaxis may be a driving force for Ang-2 induced monocyte migration. However, as described earlier, Ang-2 directly interacts with monocytes and TEMs through both Tie-2 and integrin signaling [170][171][172]. These myeloid cells, once present in a KSHV infection microenvironment, rapidly differentiated into TAMs [157,173], which, as described earlier, are well known to promote tumor growth and progression [171,174,175].…”
Section: Ang-2 Promotes Angiogenesis Inflammation and Ks Tumor Growthmentioning
confidence: 72%